Financial accounting for deferred taxes: a systematic review of empirical evidence - Anna Görlitz; Michael Dobler (Management Review Quarterly, 2021)
Deferred taxes—resulting from differences between financial and tax accounts—have been a long-standing, contentious issue in financial accounting regulation, practice, and research. Debates on concepts and standards have been accompanied by doubts around whether and the extent to which deferred taxes provide relevant information for financial statement users and are employed by firms to manage their earnings. This paper systematically reviews the body of empirical evidence that has emerged over the last three decades on deferred taxes in the fields of value relevance and earnings management. A bibliographic analysis and a narrative synthesis are presented within a thematic categorization framework. Key results indicate that existing research focuses on the US setting. There is substantial evidence for the value relevance of various deferred tax items but limited evidence that firms use deferred taxes to manage their earnings. The findings suggest implications for both future research and the regulatory debate.
Keywords: H25; M41; M48; 650; Deferred taxes; Earnings management; Income taxes; Value relevance; International Financial Reporting Standards; US Generally Accepted Accounting Principles